2011
DOI: 10.1111/j.1601-183x.2011.00702.x
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Association of upregulated Ras/Raf/ERK1/2 signaling with autism

Abstract: Autism is a neurodevelopmental disorder characterized by impairments in social interaction, verbal communication and repetitive behaviors. BTBR mouse is currently used as a model for understanding mechanisms that may be responsible for the pathogenesis of autism. Growing evidence suggests that Ras/Raf/ERK1/2 signaling plays death-promoting apoptotic roles in neural cells. Recent studies showed a possible association between neural cell death and autism. In addition, two studies reported that a deletion of a lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 56 publications
2
29
0
Order By: Relevance
“…Zou et al . demonstrated that RAS/RAF/ERK1/2 signaling was upregulated in the brains of the BTBR mouse model of autism [63]. Recently, the upregulation of this pathway (and of ERK5) has been shown to occur in the brains of autistic subjects [64].…”
Section: Discussionmentioning
confidence: 99%
“…Zou et al . demonstrated that RAS/RAF/ERK1/2 signaling was upregulated in the brains of the BTBR mouse model of autism [63]. Recently, the upregulation of this pathway (and of ERK5) has been shown to occur in the brains of autistic subjects [64].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated elevated ERK1/2 phosphorylation in whole frontal cortical homogenates of BTBR mice (Zou et al, 2011). Many studies, including our own, have shown that synaptic ERK1/ 2 phosphorylation is constitutively elevated in Fmr1 KOs (Hou et al, 2006;Michalon et al, 2012;Seese et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…We focused on ERK1/2 because (i) mutations in this kinase are associated with autism (Samuels et al, 2009), (ii) ERK1/2 levels are reportedly abnormal in BTBRs and other strains with autism-like phenotypes (Hou et al, 2006;Seese et al, 2012;Zou et al, 2011) and (iii) ERK1/2 activity is necessary for and activated by learning and memory (Thomas and Huganir, 2004). To test if ERK1/2 levels were abnormal at BTBR synapses, we employed fluorescence deconvolution tomography to quantify postsynaptic immunolabeling in CA1b fields containing B40 000 postsynaptic densities (PSDs) (Seese et al, 2013).…”
Section: Density Of Phospho-erk1/2 Is Abnormally Low In Btbr Synapsesmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, several syndromic forms of ASDs due to the effects of single major genes (e.g., tuberous sclerosis complex and fragile X syndrome) are associated with overactivation of mTOR signaling (Ehninger and Silva, 2011; Sahin, 2012; Sharma et al, 2010). Importantly, the BTBR mouse strain has upregu-lated Ras/Raf/ERK1/2 signaling, which governs activity of mTORC1 (Yang et al, 2011; Zou et al, 2011). Specifically, relative to the B6 comparator strain, BTBR mice showed increased expression of immunoreactive Ras protein in frontal cortex and cerebellum (Zou et al, 2011).…”
Section: Introductionmentioning
confidence: 99%